Joule heating effects on unsteady natural convection flow near a moving semi-infinite vertical plate with variable heat flux and mass transfer - Narahari, M. (American Institute of Physics Inc., 2016)
The unsteady MHD free convective boundary-layer flow along an impulsively started semi-infinite vertical plate with variable heat flux and mass transfer have been investigated numerically. The effects of chemical reaction, thermal radiation and Joule heating are incorporated in the governing equations. Crank-Nicolson finite-difference method is used to solve the governing coupled non-linear partial differential equations. The influence of thermal radiation, chemical reaction and Joule heating on flow characteristics are presented graphically and discussed in detailed. To validate the present numerical results, a comparison study has been performed with the previously published results and found that the results are in excellent agreement. It is found that the local Nusselt and Sherwood numbers decreases with the intensification of magnetic field and the local Sherwood number slightly decreases with the increase of radiation parameter. Â© 2016 Author(s).